Draft Annual Plan 1995-96 Daman and Diu - Planning Commission (Planning Commission, 1995)
The two districts of Daman & Diu contained in the Union Territory of Daman and Diu are separated from each other by about 800 Kms. and are sandwiched between the industrially prosperous States of Gujarat and Maharashtra. Daman & Diu were declared as industrially backward areas. However, the proximity to industrially advanced towns like Bombay, Surat, Ahmedabad, Rajkot and Bhavnagar has had some spill over effect. Besides, the picturesque territory, together with a calm and peaceful environment attract both the industrial house as well as the tourist.
Union Territory of Dadra and Nagar Haveli, Department of Planning